2020
DOI: 10.2480/agrmet.d-18-00029
|View full text |Cite
|
Sign up to set email alerts
|

Observation of vertical profiles of NO, O<SUB>3</SUB>, and VOCs to estimate their sources and sinks by inverse modeling in a Japanese larch forest

Abstract: Trace atmospheric gases in the biosphere, such as ozone O 3 , nitrogen oxides NO x , and biogenic volatile organic compounds BVOCs , can affect the carbon cycle as well as the climate. Vertical profiles of nitric oxide NO , O 3 , and volatile organic compound VOC concentrations were measured at a Japanese larch Larix kaempferi forest in the foothills of Mt. Fuji in Japan over an 11-day period in July 2012. The concentrations of NO and O 3 during the day were highest above the canopy and decreased with proximit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
(65 reference statements)
1
2
1
1
Order By: Relevance
“…Further reactions reduced MEK and 3-buten-2-ol to 2-butanol. A similar result has been reported by Tani et al 2020 , but they did not observe 3-buten-2-ol emission from non-isoprene-emitting species including three tree and one houseplant species. Cappellin et al 2019 determined the conversion ratio of MVK to MEK to be 73 , and that of MVK to all volatiles including MEK, 3-buten-2-ol, and 2-butanol to be 97.6 , suggesting that the absorbed MEK was mostly converted to volatiles and scarcely remained in leaves.…”
Section: Leaf Uptake Of Ovocssupporting
confidence: 89%
See 2 more Smart Citations
“…Further reactions reduced MEK and 3-buten-2-ol to 2-butanol. A similar result has been reported by Tani et al 2020 , but they did not observe 3-buten-2-ol emission from non-isoprene-emitting species including three tree and one houseplant species. Cappellin et al 2019 determined the conversion ratio of MVK to MEK to be 73 , and that of MVK to all volatiles including MEK, 3-buten-2-ol, and 2-butanol to be 97.6 , suggesting that the absorbed MEK was mostly converted to volatiles and scarcely remained in leaves.…”
Section: Leaf Uptake Of Ovocssupporting
confidence: 89%
“…Cappellin et al 2019 determined the conversion ratio of MVK to MEK to be 73 , and that of MVK to all volatiles including MEK, 3-buten-2-ol, and 2-butanol to be 97.6 , suggesting that the absorbed MEK was mostly converted to volatiles and scarcely remained in leaves. On the contrary, MVK conversion ratios of the non-isoprene-emitting species determined by Tani et al 2020 were much lower than those reported by Cappellin et al 2019 ; i.e. 26 -39 for MEK and 33 -44 for all volatiles.…”
Section: Leaf Uptake Of Ovocscontrasting
confidence: 72%
See 1 more Smart Citation
“…We employ O 3 -sensitive plants, such as morning glory (Ipomoea nil), as a biological indicator for avoiding O 3 stresses in a city [49]. As green area (trees and shrubs) has a high capacity for improvement of O 3 that is detected by flux monitoring [12,50,51], the green area has higher removal capacity (3.4 g m À2 yr. À1 on average) than green roofs (2.9 g m À2 yr. À1 as average removal rate), with lower installation and maintenance costs [13]. To overcome present gaps and uncertainties, they proposed a novel species air quality index (S-AQI) of suitability to air quality improvement for tree/shrub species.…”
Section: Figurementioning
confidence: 99%
“…法获取大气边界层内 VOCs 物种浓度的垂直分布数据 [39,40] 。随着民用无人机产业的快速发 展,许多性能优异(载荷大、续航时间长和操控稳定度高等)且价格低廉的中小型无人机被 广泛用于大气监测领域,获取边界层内各类大气参数的垂直分布数据 [41] 。无人机是近些年来 较为热门的大气垂直观测平台,基于无人机平台的各种优异性能,其在大气垂直观测领域有 广阔的应用前景。 无人机平台的优点在于其机动灵活性较高,能够在复杂环境中使用 [42] ,对后勤保障和观 测场地的要求较低,且其使用成本也相对低廉 [43] 。使用电池驱动的无人机可以有效避免燃油 废气排放对 VOCs 观测样本可能造成的污染,提高观测数据的可靠性 [44][45][46] 。虽然无人机平台 具有较好的操控性和灵活机动性,但也存在诸多因素限制。首先,受当前电池技术发展的限 制,无人机的续航时间仍然不足,有效载重较小,并且续航时间随附加设备重量的增加而急 剧下降 [47] ,严重限制了一个航次中能够有效获取的观测样本数量;其次,无人机平台主要使 用离线分析方法获取 VOCs 物种浓度的垂直分布数据,数据的时空分辨率通常较低 [48] [49][50][51] 。 比如, Zhou 等人研发的空气检测传感器 (Kolibri) 就是应用于无人机上的低成本检测传感器,它包括 VOCs 和颗粒物采集器以及黑炭分析仪 [49] 。Chen 等人设计用于无人机平台的苏玛罐采集系统,这种无人机有效载荷 1 kg,能满足 250 m 以下采样需求 [50] 。 1.5 遥感技术 遥感技术可以分为卫星遥感和地面遥感, 地面遥感技术主要使用激光雷达遥感 (Lidar) 和差分吸收光谱技术(DOAS) 。卫星遥感是借助传感器对远距离环境辐射和反射的电磁波 信号进行收集与处理 [52] ;激光雷达遥感是向目标发射激光束,将反射信号与发射信号比较并 适当处理,获取 VOCs 浓度的垂直分布数据 [53][54][55] 。 遥感技术作为长期稳定的监测手段,能及时反馈地球大气中关键 VOCs 组分浓度的时 空分布信息,例如卫星遥感能够能检测到乙二醛和甲醛的垂直柱浓度,并且能够监测全球范 围内 VOCs 浓度空间分布的实时变化 [56] 。但由于各类遥感技术的原理不同,空气中的颗粒 物和水蒸气等能对遥感信号造成干扰,因此遥感技术的准确性受到限制 [57] ;此外,使用遥感 技术测量的 VOCs 种类受到限制,目前遥感技术主要用于对流层大气中甲醛、乙二醛和一些 芳香烃的测量 [58,59] 。 卫星遥感能长期监测大范围空间内的 VOCs 变化特征 [60] ,常与模型计算结果进行对比 分析,以提高模拟结果的准确性 [61] 。比如,借助卫星平台的高空间分辨率遥感数据,研究人 员能够有效分析区域燃烧源相关 VOCs 的排放清单并加以验证 [62] ;DOAS 通常用于测量区 域甲醛和乙二醛的垂直柱浓度, 研究关于它们的大气化学过程 [63] [65] 和人为源(如工厂和机动车排放等) [66] 。源排放类型分为移动源 和固定源,移动源(如机动车)影响地面 VOCs 浓度 [67] ;固定源除了影响地面 VOCs 浓度 [68] 外,也影响 VOCs 垂直分布 [69][70][71] 。如 Wada 等人发现富士山上的 VOCs 垂直分布结构受到周 边森林排放 VOCs 影响 [69] ;Zhang 等人发现上海机动车排放高浓度的苯,导致地面 200 m 内 出现多个峰值 [71] 。当区域地面污染源排放结构存在显著差异时,关键 VOCs 物种和其他污 染物(如 NO X 和一氧化碳等)的垂直分布结构也出现显著的空间分布差异…”
Section: 无人机平台 无人机平台以无人驾驶飞行器(包括固定翼和多旋翼等)为依托,通常使用离线分析方unclassified